Respostas
respondido por:
109
Boa tarde
5x - 15y + z = -4
5*4α - 15α - 3α = -4
20α - 15α - 3α = -4
20α - 18α = -4
2α = -4
α = -4/2 = -2
5x - 15y + z = -4
5*4α - 15α - 3α = -4
20α - 15α - 3α = -4
20α - 18α = -4
2α = -4
α = -4/2 = -2
Madsoncosta7:
Muito obrigado, você me ajudou muito :))
respondido por:
14
5x - 15y + z = -4
5*4α - 15α - 3α = -4
20α - 15α - 3α = -4
20α - 18α = -4
2α = -4
α = -4/2 = -2
Perguntas similares
6 anos atrás
6 anos atrás
6 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás